Prognostic value of immunoscore to identify mortality outcomes in adults with HBV-related primary hepatocellular carcinoma. Issue 17 (April 2017) - Yao, Qinwei; Bao, Xuli; Xue, Ran; Liu, Hui; Liu, Haixia; Li, Juan; Dong, Jinling; Duan, Zhonghui; Ren, Meixin; Zhao, Juan; Song, Qi; Yu, Hongwei; et al.
Abstract : Abstract: This study aimed to determine if the immunoscore (IS) staging system would be a potential prognostic factor in hepatitis B virus-related hepatocellular carcinoma (HBV-HCC) in China. IS was performed in a consecutive cohort of HBV-HCC patients (n= 92). CD3+, CD8+, and CD45RO+ T cells were quantified by immunohistochemical analyses. The patients were stratified into 5 IS groups: I0, I1, I2, I3, I4 for every 2 cell phenotypes (IS1 (CD8/CD45RO, IS2 (CD3/CD8), and IS3 (CD3/CD45RO), respectively. ImagePro Plus software was used in the calculation of the paraffin-embedded tumor sections. The staining of CD3+, CD8+, and CD45RO+ cells in the HBV-HCC tissue demonstrated that there were higher density and larger area of lymphocytes in the invasive margins (IM) region than in the center (CT). Univariate analysis showed that preoperative TNM staging ( P = .01), serum gamma-glutamyl transpeptidase (GGT) level ( P = .03), vascular invasion ( P = .00), and density of CD3+T (CT) ( P = 0.01) were correlated significantly with disease-free survival (DFS); serum alpha-fetoprotein (AFP) level ( P = .02), tumor size ( P = .00), serum cholinesterase (CHE) ( P = .04), and GGT level ( P = .01), density of CD3+T(CT) ( P  = .00), CD8+T(CT)( P  = .00), CD45RO+T(CT) ( P  = .00), and CD45RO+T (IM) ( P  = .02) were correlated with overall survival (OS). Multivariate analysis showed that TNM staging was not an independent prognostic factor of DFS and OS. Our results showed ISs did not have a significantly correlation with DFS ( P  = .35, .19, and .07, respectively), but it was correlated significantly with OS ( P  = .00, .00, and .00, respectively). There were statistical differences among the OS of every ISs subgroup except I0 and I1 by the Cox regressions analysis. The IS staging was closely related to the outcome of patients. It can compensate the TNM tumor classification system in predicting the prognosis of HBV-HCC patients.